Teach yourself visually Photoshop CS4 - Wooldridge, Mike (Visual read less, learn more., 2009)
"If you learn best visually, then you'll love the updated and expanded coverage found in this tutorial. An approachable teaching style makes Photoshop CS4 accessible for beginners and instructs visual learners of how to put this application to work for them"--Resource description page